The clinician`s guide to baseball pitching biomechanics - Diffendaffer, A. Z.; Bagwell, M. S.; Fleisig, G. S.; Yanagita, Y.; Stewart, M.; Cain, E. L.; Dugas, J. R.; Wilk, K. E. (Sports Health: A Multidisciplinary Approach, 2023)
Context: Improper baseball pitching biomechanics are associated with increased stresses on the throwing elbow and shoulder as well as an increased risk of injury.